Complete Blood Collection-based Systemic Inflammation Biomarkers as a Severity Biomarker in Alopecia Areata: A Cross-sectional Study - Sihan Deng; Jundong Huang; Min Li; Jia Jian; Wei Shi (Medical Journals Sweden, 2024)
Previous studies have suggested that alopecia areata (AA) is an organ-specific disease characterized by loss of immune privilege of hair follicles. However, an increasing body of research indicates that it not only affects the skin but may also be accompanied by systemic inflammatory reactions. Therefore, searching for simple and easily available biomarkers to describe the underlying systemic inflammation in AA patients is of great clinical significance. Complete blood collection-based systemic inflammation biomarkers have been shown to be associated with the severity and prognosis of various skin and autoimmune diseases. They involve multiple cell lineages and can reveal different pathways of immune-inflammatory responses. The aim of this study was to investigate the level of complete blood collection-based systemic inflammation biomarkers in patients with AA, and to analyse their relationship with the disease severity. A total of 302 AA patients and 296 healthy controls were included in this study and the neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), systemic immune inflammation index (SII), and white blood cell/lymphocyte ratio (WLR) were calculated. The differences in these indicators between the 2 groups were compared, and the relationship between NLR, PLR, SII, WLR, and the risk of severe AA were analysed. AA patients had higher NLR, SII, and WLR compared with healthy controls (p = 0.004, 0.002, and 0.002 respectively). PLR and SII were higher in the severe AA group compared with the mild-to-moderate AA patients (p = 0.005 and 0.011 respectively). The risk of severe AA increased with the increasing of PLR, SII, NLR, and WLR (p for trend was 0.001, 0.006, 0.022, and 0.021, respectively). The levels of systemic inflammation biomark-ers in AA patients are higher than in healthy people. NLR, PLR, SII, and WLR are risk factors for severe AA, suggesting a close association between systemic inflammation and disease occurrence in AA patients.